Divide and Conquer: Phenotypic and Temporal Heterogeneity Within CD8+ T Cell Responses - Richard, Arianne C. (Frontiers in Immunology, 2022)
The advent of technologies that can characterize the phenotypes, functions and fates of individual cells has revealed extensive and often unexpected levels of diversity between cells nominally of the same subset. CD8+ T cells, also known as cytotoxic T lymphocytes (CTLs), are no exception. Investigations of individual CD8+ T cells both in vitro and in vivo have highlighted the heterogeneity of cellular responses at the levels of activation, differentiation and function. This review takes a broad perspective on the topic of heterogeneity, outlining different forms of variation that arise during a CD8+ T cell response. Specific attention is paid to the impact of T cell receptor (TCR) stimulation strength on heterogeneity. In particular, this review endeavors to highlight connections between variation at different cellular stages, presenting known mechanisms and key open questions about how variation between cells can arise and propagate.